Vanadium metal‐organic framework‐derived multifunctional fibers for asymmetric supercapacitor, piezoresistive sensor, and electrochemical water splitting. Issue 4 (1st February 2022) - Pu, Jie; Gao, Yong; Cao, Qinghe; Fu, Gangwen; Chen, Xing; Pan, Zhenghui; Guan, Cao
Abstract: Fiber‐shaped integrated devices are highly desirable for wearable and portable smart electronics, owing to their merits of lightweight, high flexibility, and wearability. However, how to effectively employ multifunctional fibers in one integrated device that can simultaneously achieve energy storage and utilization is a major challenge. Herein, a set of multifunctional fibers all derived from vanadium metal‐organic framework nanowires grown on carbon nanotube fiber (V‐MOF NWs@CNT fiber) is demonstrated, which can be used for various energy storage and utilization applications. First, a fiber‐shaped asymmetric supercapacitor (FASC) is fabricated based on the CoNi‐layered double hydroxide nanosheets@vanadium oxide NWs@CNT fiber (CoNi‐LDH NSs@V2 O5 NWs@CNT fiber) as the positive electrode and vanadium nitride (VN) NWs@CNT fiber as the negative electrode. Benefiting from the outstanding compatibility of the functional materials, the FASC with a maximum working voltage of 1.7 V delivers a high‐stack volumetric energy density of 11.27 mW·h/cm 3 . Then, a fiber‐shaped integrated device is assembled by twisting a fiber‐shaped piezoresistive sensor (FPS; VN NWs@CNT fiber also served as the highly sensitive material) and a FASC together, where the high‐performance FASC can provide a stable and continuous output power for the FPS. Finally, the S‐VO x NWs@CNT fiber (sulfur‐doped vanadium oxide) electrode shows promising electrocatalytic performance for both hydrogen evolution reaction (HER) and oxygen evolution reaction (OER), which is further constructed into a self‐driven water‐splitting unit with the integration of the FASCs. The present work demonstrates that the V‐MOF NWs@CNT‐derived fibers have great potential for constructing wearable multifunctional integrated devices. Abstract : Multifunctional fibers derived from vanadium metal‐organic framework nanowires grown on carbon nanotube fiber (V‐MOF NWs@CNT fiber) are simultaneously employed in fiber‐shaped asymmetric supercapacitor (FASC), piezoresistive sensor (FPS), and electrochemical water splitting. The FASC/FPS‐integrated device and self‐driven water‐splitting unit (FASC serving as a power supply), prove that the V‐MOF NWs@CNT fiber holds great potential for the construction of high‐performance multifunctional integrated electronics.